2006
DOI: 10.1111/j.1601-0825.2005.01193.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of basement membrane components in odontogenic cysts

Abstract: Substantial differences in the expression of BMCs among studied cysts were not observed, suggesting that the separation of the epithelial lining in OKCs is not associated with the existence of these proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 36 publications
5
18
1
1
Order By: Relevance
“…15 Many extracellular matrix substrates for matrilysins are epithelial and vascular basement membrane components, such as, laminin, fibronectin, and type IV collagen. 2,12,35 Thus, the immunoreactivity of the SOKC and NSOKC epithelial cells to MMPs-7 and Ϫ26 observed in this research corroborate the results reported by other studies that analyzed basement membrane composition in the OKC epithelial-connective tissue junction.…”
Section: Table II Immunoreactivity To Matrix Metalloproteinases In Osupporting
confidence: 90%
See 2 more Smart Citations
“…15 Many extracellular matrix substrates for matrilysins are epithelial and vascular basement membrane components, such as, laminin, fibronectin, and type IV collagen. 2,12,35 Thus, the immunoreactivity of the SOKC and NSOKC epithelial cells to MMPs-7 and Ϫ26 observed in this research corroborate the results reported by other studies that analyzed basement membrane composition in the OKC epithelial-connective tissue junction.…”
Section: Table II Immunoreactivity To Matrix Metalloproteinases In Osupporting
confidence: 90%
“…This finding led the authors to suggest that type IV collagen discontinuity, together with altered expression of other extracellular molecules in the OKC epithelial basement membrane could be involved in the aggressive biological behavior of this lesion. The presence of matrilysins in the SOKC and NSOKC epithelial component observed in our study may account for the weak and discontinuous pattern of type IV collagen expression along OKC epithelial basement membranes, as reported by Oliveira et al 2 and Poomsawat et al 35 Despite the absence of statistical differences (P Ͼ .05) in epithelial immunoreactivity to MMPs-7 and Ϫ26 between SOKCs and NSOKCs, our results showed a tendency for a more consistent expression of these proteases in SOKCs. Comparing the samples, 100% of the SOKC cases showed epithelial immunoreactivity to MMPs-7 and Ϫ26, whereas only 75% and 80% of NSOKC cases had epithelial immunohistochemical expression of matrilysins 1 and 2, respectively.…”
Section: Table II Immunoreactivity To Matrix Metalloproteinases In Osupporting
confidence: 67%
See 1 more Smart Citation
“…ECM proteins have been detected in several odontogenic cysts and tumors, 7,8,[17][18][19] but no investigation has explored the relationship between collagen IV, MMPs, and TIMPs in odontogenic cysts and tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is possible that this BM irregularity shown by KOTs favors the constant shedding of epithelial cells from the capsule and may be related to the higher recurrence rates of these tumors. Although consensus exists regarding the relationship between BM integrity and aggressiveness of the lesion, Poomsawat et al 19 found no association between the expression of BM components (laminin 1 and 5, collagen IV, and fibronectin) in RCs, DCs, and KOTs and the biologic behavior of these lesions. Therefore, in view of the functions of the BM, especially its involvement in the control of cell proliferation, differentiation, and invasion, it is evident how much these processes are altered in KOTs and ameloblastomas, a fact that can explain the more aggressive behavior of these tumors compared with RCs and DCs.…”
Section: Discussionmentioning
confidence: 99%